2005
DOI: 10.1002/pola.21161
|View full text |Cite
|
Sign up to set email alerts
|

Homo‐ and copolymerization of methyl methacrylate with ethylene by novel Ziegler‐Natta‐Type nickel catalysts based on N,O‐nitro‐substituted chelate ligands

Abstract: New Nickel (II) catalytic systems based on N,O chelate ligands, activated by methylaluminoxane, have been checked in the homopolymerization of methyl methacrylate (MMA) and its copolymerization with ethylene. In particular, the bis(8‐hydroxy‐5‐nitro‐quinolate)nickel(II)/methylaluminoxane system as well as the catalysts obtained by oxidative addition of either 8‐hydroxy‐5‐nitro‐quinoline or 8‐hydroxy‐5,7‐dinitro‐quinoline or 4‐nitro‐2‐(p‐nitrobenzylideneamino)‐phenol to Ni(cod)2, subsequently activated by methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…Unlike other reported catalytic nickel complexes with O,N-containing ligands [13,14], the present two nickel complexes require merely either AlEt 3 or Al(i-Bu) 3 and AlEt 2 Cl as cocatalysts for the polymerization of MMA. Polymerization to produce PMMA and the effect of three cocatalysts on MMA polymerization with an Al/Ni ratio 400 and at 30°C furnishes results ( Table 3) that prove that the three alkylaluminiums can initiate the reaction.…”
Section: Cocatalystmentioning
confidence: 77%
See 1 more Smart Citation
“…Unlike other reported catalytic nickel complexes with O,N-containing ligands [13,14], the present two nickel complexes require merely either AlEt 3 or Al(i-Bu) 3 and AlEt 2 Cl as cocatalysts for the polymerization of MMA. Polymerization to produce PMMA and the effect of three cocatalysts on MMA polymerization with an Al/Ni ratio 400 and at 30°C furnishes results ( Table 3) that prove that the three alkylaluminiums can initiate the reaction.…”
Section: Cocatalystmentioning
confidence: 77%
“…These systems were obtained by oxidative addition of salicylaldimine ligands to [Ni(cod) 2 ] (cod = 1,5-cyclooctadiene) and subsequent activation with MAO [14,15]. The systems of some naphtocyimine-nickel complexes/MAO were reported that can catalyze norbornene to polymerization with high catalytic activity [16,17], but there are little reports that these catalyst systems are utilized for polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%
“…Under standard conditions and adding five equivalent (per metal) of TEMPO as a free radical inhibitor, polymer yield, and catalyst productivity remained substantially the same, thus indicating that the polymerization of MMA may not occur via a radical mechanism. It was reported that the polymerization of MMA by Ni(acac) 2 [31] and salicylaldiminate nickel complexes [8][9][10] with MAO proceeds by a coordinationinsertion mechanism. Triad testes may be a good clue to differentiate between enantiomorphic site control and chain end control.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…However, only a limited number of catalysts based on late transition metals have been used for homo-and copolymerization of MMA. Ni(acac) 2 /methylaluminoxane (MAO) [7], Ni(II) complexes bearing N,O-chelate ligands activated with MAO [8][9][10], a-diimine Ni(II), and pyridyl bisimine Fe(II) and Co(II) complexes activated with MAO [11,12] yielded poly(methyl methacrylate) (PMMA) with syndiorich microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel (II) complexes bearing N, O-chelate ligand activation for MMA polymerization yielded poly (methyl methacrylate) (PMMA) with rich syndiotacticity microstructure [4][5][6][7][8][9][10]. The chelating polymers find applications in bioinorganic industry [11], wastewater treatment [12,13], pollution control [14], hydrometallurgy [15], preconcentration [16], anionic polyelectrolyte hydrogels [17], cation-exchange resins [18] , showed potential applications in material science as conductive [19], luminescent [20], magnetic, porous, chiral or non-linear optical materials [21], catalytic [22][23][24][25],organic synthesis [26], polymer drug graft, recovery of trace metal ions [13] and antimicrobial activities [27,28].…”
Section: Introductionmentioning
confidence: 99%